Evolusi Filsafat Islam: Menjembatani Kearifan Kuno dan Pemikiran Kontemporer - Wardani, Azmi Putri Ayu; Soleh, Achmad Khudori (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2024)
The development of Islamic philosophy is often claimed as a golden bridge by some orientalists, as a result of which many assumptions conclude that Islam has no philosophy and is even considered irrational. However, Islamic philosophy has its own originality and has undergone a long development and experienced the ups and downs of debates between groups. Therefore, this research aims to: (1) trace the main factors in the development of Islamic philosophy; (2) explore the development, differences, and changes in Islamic philosophical thought; (3) examine the shift in Islamic philosophical thought. The method applied is a qualitative method, with a literature-based data collection method, and analysed by content analysis or context. The results showed that; (1) the main factor that became the initial foundation and even provided ammunition for the development of Islamic philosophy was the process of translating Greek monumental works starting from the Umayyad caliphate, especially during the time of Abdul Malik (685-705) to the Abbasid caliphate which reached its heyday during the time of al-Makmun (813-833); (2) the development of Islamic philosophical thought was supported by a number of figures who had integrated philosophy with religion, such as al-Kindi (806-875), al-Farabi (872-951), Ibn Sina (980-1037), and Ibn Rushd (1126-1198); (3) On the other hand, Islamic philosophical thought also experienced rejection and criticism by a number of fiqh scholars, such as Ahmad Ibn Hanbal (806-875), al-Ghazali (1058-1111), and Ibn Taymiyyah (1263-1328).